Evaluation of phage-based decontamination in respiratory intensive care unit environments using ddPCR and 16S rRNA targeted sequencing techniques - Shi, Yinghan; Zhang, Weihua; Li, Lina; Wu, Wencai; Li, Mengzhe; Xiao, Kun; Wang, Kaifei; Sheng, Zhaojun; Xie, Fei; Wang, Xiuli; Shi, Xin; Tong, Yigang; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundKlebsiella pneumoniae is a major cause of hospital-acquired infections (HAIs), primarily spread through environmental contamination in hospitals. The effectiveness of current chemical disinfectants is waning due to emerging resistance, which poses environmental hazards and fosters new resistance in pathogens. Developing environmentally friendly and effective disinfectants against multidrug-resistant organisms is increasingly important.MethodsThis study developed a bacteriophage cocktail targeting two common carbapenem-resistant Klebsiella pneumoniae (CRKP) strains, ST11 KL47 and ST11 KL64. The cocktail was used as an adjunctive disinfectant in a hospital’s respiratory intensive care unit (RICU) via ultrasonic nebulization. Digital PCR was used to quantify CRKP levels post-intervention. The microbial community composition was analyzed via 16S rRNA sequencing to assess the intervention’s impact on overall diversity.ResultsThe phage cocktail significantly reduced CRKP levels within the first 24 hours post-treatment. While a slight increase in pathogen levels was observed after 24 hours, they remained significantly lower than those treated with conventional disinfectants. 16S rRNA sequencing showed a decrease in the target pathogens’ relative abundance, while overall species diversity remained stable, confirming that phages selectively target CRKP without disrupting ecological balance.DiscussionThe findings highlight the efficacy and safety of phage-based biocleaners as a sustainable alternative to conventional disinfectants. Phages selectively reduce multidrug-resistant pathogens while preserving microbial diversity, making them a promising tool for infection control.